Socio-Economic Demographics and Health Status of the Residents of a Hinterland Community in Negros Island, Philippines - Sorongon, Chris G.; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
This study examined the socioeconomic demographics and health status of residents in a hinterland community in Guihulngan City, Negros Island, Philippines. The research utilized the RAND 36-Item Health Survey to collect data from 163 household heads, measuring eight health concepts: physical functioning, bodily pain, role limitations (physical and emotional), emotional well-being, social functioning, energy/fatigue, and overall health perceptions. The findings revealed that the community faces socioeconomic challenges, including low educational attainment, limited employment opportunities, and reliance on government assistance. Despite these challenges, residents reported good overall health status, highlighting the potential influence of factors beyond socioeconomic demographics, such as lifestyle choices, social support, and access to healthcare. The study also identified variations in health status based on age, employment status, family monthly income, and weight, emphasizing the complex interplay of various social determinants. The research concludes by emphasizing the need for targeted interventions that address the specific needs of vulnerable groups and promote health equity in hinterland communities.